Implementasi Sistem Informasi Manajemen Aplikasi Pesona Tanah Datar Pada Dinas Pariwisata Pemuda Dan Olahraga Kabupaten Tanah Datar - Ratih Oktayuresti; Syamsir Syamsir; Windi Kurnia Putri; Widea Pitaloka; Wike Putri Meilia; Zidane Alfarizi (Universitas Palangka Raya, 2022)
The management information system in the form of the “Pesona Tanah Datar” application is part of Digital Governance which aims to realize good governance by utilizing technology. Modern tourism really needs technology for marketing, documentation and data collection which is very important to support the development of tourism as well as providing information services to the public regarding tourism, youth and sports in Tanah Datar district. applicable tourism information to support and develop regional tourism. This tourism information system will provide optimal value benefits when used in conjunction with a good tourism website and tourism multimedia. This study aims to determine the Implementation of the Pesona Tanah Datar Application Management Information System at the Youth and Sports Office of Tanah Datar Regency. In this study the authors used a descriptive qualitative research type. Data collection was not guided by theory, but guided by facts found in the field. Therefore, the data analysis carried out is inductive based on the facts found and can then be constructed into hypotheses and theories. The results showed that the implementation of a flat land charm management information system at the Department of Tourism, Youth and Sports went well.